Mobile Application for Hearing Impaired Based on Cordova Framework and Web Technologies - Azwa Mohamed Ozir, Noor; Amin Embi, Mohamed; Mohd Ali, Manisah (International Journal of Engineering and Technology, 2018)
This paper will be looking at the design and development process of GRAMMROOM, a mobile application specifically aimed to aid the hearing impaired students in mastering English Language grammar skills. GRAMMROOM is build based on the Cordova framework incorporated with the web technologies. Cordova is chosen instead of any other open-source mobile development framework as it is stable and it allows the using of standard web technologies for the cross-platform development. This is just like creating a normal web application and is very helpful for  novice developers who are at the beginning stage of developing a mobile application. GRAMMROOM will run on Android mobile phones and it is hoped that the hearing impaired students and those involved in the teaching and learning of the hearing impaired will benefit much from it.